Impact of Capital Structure on Financial Performance of listed Insurance firms in Nigeria - Ojochegbe, Agada Sunday; Mathew, Akyenyi Emmanule; Adebayo, Habeebat Umar (Kashere Journal of Management Sciences, 2024)
This study examines the impact of capital structure on financial performance of listed insurance firms on the Nigerian Stock Exchange. The study adopted an ex-post facto research design and utilized panel data collected from annual reports and accounts of the sampled firms for the periods of 2013 to 2017. The Data was analyzed using a panel data regression technique to examine the extent of the impact of capital structure on the financial performance of Nigerian insurance companies. It was found out that capital structure proxied by retained earnings, debt and equity has significant impact on financial performance measured by return on asset (ROA) of listed insurance companies in Nigeria. Thus, the study concludes that statistically, capital structure is a major determinant of firm financial performance. Therefore it is recommended that managers of the companies should exercise caution while choosing their capital structure as it affects their performance and more effort to be geared toward internally providing additional capital than to look for debt.